الأبعاد العقائدية في قصة النبي موسى ( عليه السلام ): الدعاء إنموذجاً - محيي، أنسام زيد Mohi, Ansam Zaid (جامعة ذي قار - كلية التربية للعلوم الإنسانية, 2018)
This article focuses on the supplication in the story of Prophet Moses (peace be upon him), through events and news in the Quranic stories, we have tried to monitor within certain hubs, and note their integration with each other to form in the end the basic aim of the article that tires to demonstrate the impact of supplication in the story of Moses (peace be upon him), the call in the cause of Allah, through the consolidation of the principle of singling out Allah in the supplication, and to respond to its uniqueness, as well as rooting the spiritual relationship between a person and his Creator, which has a dramatic impact on the consolidation of belief and loyalty to God Almighty lay the base. After reviewing the evidence in the Quranic story of Prophet Moses, (peace be upon him) shows us the importance of supplication and its place, and the human needs it, rooting in some aspect associated closely dogmatic rules, which has a dramatic impact on several aspects of life, including the mundane and eschatological.
ركز البحث على الدعاء في قصة النبي موسى (عليه السلام)، من خلال الأحداث والأخبار في القصص القرآنية، محاولا رصدها ضمن محاور معينة، وملاحظة تكاملها مع بعضها لتشكل في النهاية الهدف الأساسي من البحث، إذ هدف البحث إلى بيان أثر الدعاء في قصة النبي موسى (عليه السلام)، في الدعوة إلى الله تعالى، من خلال ترسيخ مبدأ إفراد الله تعالى بالدعاء، وتفرده بالاستجابة، فضلا عن تأصيل للعلاقة الروحية بين العبد وخالقه، مما له بالغ الأثر في ترسيخ العقيدة وإرساء قاعدة الولاء لله تعالى. وبعد استعراض الشواهد القرآنية في قصة النبي موسى عليه السلام يتبين لنا أهمية الدعاء ومكانته، وحاجة الإنسان إليه، في تأصيل بعض القواعد المرتبطة بالجانب العقائدي ارتباطا وثيقا، مما له بالغ الأثر في جوانب الحياة الدنيوية منها والأخروية.
Keywords: العقيدة الإسلامية -- قصص القرآن -- قصة النبي موسى عليه السلام -- الدعاء -- الدعوة الإسلامية